2020
DOI: 10.1016/j.cels.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Fluorescent E. coli Lysogens Allow Live-Cell Imaging of Functional Prophage Induction Triggered inside Macrophages

Abstract: Highlights d A bacteriophage lysis reporter allows for live-cell imaging of prophage induction d Macrophages trigger l phage induction and lysis in phagocytosed E. coli through PhoP d Induced l phage can propagate secondary E. coli infections inside phagosomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 59 publications
0
19
1
Order By: Relevance
“…It is a sensor of environmental stress including low Mg 2+ levels, antimicrobial peptides, and acidic pH. It was suggested that phages may interact with the innate immune system (Figure 7) [255].…”
Section: Interactions Between Prophages and Eukaryotic Cellsmentioning
confidence: 99%
“…It is a sensor of environmental stress including low Mg 2+ levels, antimicrobial peptides, and acidic pH. It was suggested that phages may interact with the innate immune system (Figure 7) [255].…”
Section: Interactions Between Prophages and Eukaryotic Cellsmentioning
confidence: 99%
“…In the vacuolar compartment, Lambda induction was not dependent on RecA, as observed in vitro , but rather on PhoP. An anti-microbial peptide, mCramp1, was suggested to be at the origin of this induction, via a bacterial membrane stress (15). Whether prophages from natural E. coli isolates are also induced and provoke bacterial lysis in macrophages remains unknown.…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, it was recently established that the macrophage environment can provoke Lambda prophage induction by 26-fold compared to in vitro in an unstimulated model laboratory E. coli strain (15). This high induction level, which leads in vitro to the lysis of ∼90% of the bacteria, probably facilitates the clearing work of macrophages (15). In the vacuolar compartment, Lambda induction was not dependent on RecA, as observed in vitro , but rather on PhoP.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these proinflammatory effects, there are indications that phages may act synergistically with the innate immune response to promote bacterial clearance. Using an innovative fluorescent lysis reporter system, Bodner et al (101) detected lysis of E. coli by a lambda prophage in response to ROS present within a macrophage phagosome. This suggests that phages provide an alternative bacterial killing pathway for macrophages.…”
Section: Phages and Bacterial Clearancementioning
confidence: 99%